Three essays in financial economics: regulation, supervision and lenders' behaviour - Nguyen, Huyen N.P. (2019)
This thesis contributes to the literature on the unintended consequences of financial reg-ulation. Throughout the thesis, I ask three independent yet related research questionsaiming to empirically understand how lenders restructure their balance sheets throughlending and securitization under exogenous regulatory and supervisory shocks. My first paper examines whether financial institutions use securitization to shift theircredit default risk to Government Sponsored Enterprises (Fannie Mae and Freddie Mac)more frequently when they bear higher expected cost of default created by borrowerfriendly foreclosure laws in the United States (US). Using a geographical regression discon-tinuity design, I document that lenders are more likely to securitize GSE-eligible mortgageloans when subject to borrower-friendly foreclosure law. The paper points out that bor-rower friendly foreclosure laws lead to unintended consequences of raising US taxpayers’exposure to the housing market of $140bn per annum. In the second paper, I exploit the interstate branching deregulation in the US as a naturalexperiment and answer a novel research question: “Does competition policy increase secu-ritization in the lead up to the financial crisis?”. I document that more intense competitionfollowing the relaxation of branching restrictions increases the cost of deposits, which inturn, motivates banks to switch from the “originate-to-hold” to “originate-to-distribute”model. Evidence using mortgage level analysis also suggests that the probability that abank sells a mortgage loan in the secondary market is significantly higher in the face ofderegulation. The findings highlight a hitherto neglected factor behind the rapid expansionin securitization before the financial crisis. My third paper looks at how supervisory actions under the German stress testing frame-work affect bank lending. Exploiting supervisory requirements in maximum unexpectedeconomic losses due to interest rate risk a bank can incur as sharp thresholds for moni-toring and capital surcharges, I find that greater supervisory monitoring does not affectlending behaviour but mandatory capital surcharges significantly reduce bank lending.The contraction in lending is most pronounced for corporate loans, mortgage loans, andfor loans with longer maturities.